Aspen plus : chemical engineering applications - Al-Malah, Kamal I. M. (Wiley, 2022)
"This updated edition focuses on the latest software version of Aspen Plus V12 covering new features that were embedded into the software and existing features which have been modified. Each chapter includes a running tutorial and demo via an image-augmented text that covers one or more of the common unit operations or chemical processes found in chemical industries. Additionally, this edition features a new chapter for advanced users who can build/customize their own model made of up of sets of both algebraic and differential equations. With concise instructions and step-by step tutorials, readers will quickly become successful users of Aspen Plus with this book as their guide. An instructor's solutions manual is available for end of chapter problems, making this book ideal for students and professionals in chemical engineering,"--